Vegan diets: practical advice for athletes and exercisers - Rogerson, D. (Journal of the International Society of Sports Nutrition, 2017)
With the growth of social media as a platform to share information, veganism is becoming more visible,and could be becoming more accepted in sports and in the health and fitness industry. However, to date, thereappears to be a lack of literature that discusses how to manage vegan diets for athletic purposes. This article attemptedto review literature in order to provide recommendations for how to construct a vegan diet for athletes and exercisers.While little data could be found in the sports nutrition literature specifically, it was revealed elsewhere that veganismcreates challenges that need to be accounted for when designing a nutritious diet. This included the sufficiency ofenergy and protein; the adequacy of vitamin B12, iron, zinc, calcium, iodine and vitamin D; and the lack of thelong-chainn-3 fatty acids EPA and DHA in most plant-based sources. However, via the strategic management of foodand appropriate supplementation, it is the contention of this article that a nutritive vegan dietcanbe designed toachieve the dietary needs of most athletes satisfactorily. Further, it was suggested here that creatine andß-alaninesupplementation might be of particular use to vegan athletes, owing to vegetarian diets promoting lower musclecreatine and lower muscle carnosine levels in consumers. Empirical research is needed to examine the effects of vegandiets in athletic populations however, especially if this movement grows in popularity, to ensure that the health andperformance of athletic vegans is optimised in accordance with developments in sports nutrition knowledge.